Taxonomy of Values and Anti-Values: the Material of the Russian and German Phraseology - Andreyeva, Elena A.; Nazmieva, Elmira I.; Nasrtdinova, Valentina M. (Journal of History Culture and Art Research, 2017)
At present, in terms of intercultural communication, the role of the axiological aspect in teaching foreign languages is growing. When thinking about the values and anti-values in the phraseology of Russian and German it is advisable to take into account their hierarchy which can be presented as the axiological scale. This investigation benefits from the following methods: axiological linguistic method, method of cognitive analysis, comparative method, processing of lexicographical sources. The result of the study is formation of the axiological scale and development on its basis of the taxonomic model of values and anti-values in the phraseology of the Russian and German languages. The taxonomic model of values and anti-values in the phraseology of the language allows submitting axiological hierarchy reflecting the inter-layer differentiation of values and anti-values represented by axiological phraseology. Axiological scale and taxonomic model of values and anti-values in the Russian and German phraseology can be used in linguistic axiological research of different languages.